Pathology and surgery of bell's palsy: A report of 108 cases subjected to the ballance-duel operation - Karsten Kettel (Arquivos de Neuro-Psiquiatria)
The majority of cases of Bell's palsy are due to ischaemia of the facial nerve near the stylomastoid foramen. Following lack of blood supply the nerve loses its power of conduction, and venous stasis arises with ensuing swelling of the nerve, which becomes secondarily compressed within the Fallopian canal. The therapy of choice is medical treatment aiming to relieve the vasoconstriction and maintain the contractility of the muscles. Surgical decompression of the facial nerve is indicated in a limited number of cases, and the results of 108 operations are briefly recorded. Decompression should be performed in both fresh and relapsing palsies if no signs of spontaneous movement are observed after two months of observation. With patients in whom spontaneous recovery has ceased be-fored complete restitution has been obtained, further improvement may be expected from decompression.